The influence of compassion in Charles Dickens’ selected novels - Mohd Nazri, Latiff Azmi; Ali Mahmoud, Ali Alshwayyat; Mohammad Nusr, Mohammad Al Subaihi (2020)
The novel shall include different personalities to have a compelling story knot, which shall tighten the reader to read the story and even get touched with it. In Charles Dickens’ novels particularly, which usually resembles agony, poverty, and suffering, a compassion side of the society of the novel shall be presented in contrast to suffering. This paper is presenting three common novels by Dickens, A Tale of Two Cities, Oliver Twist and David Copperfield. It deals with the comparison between the personalities which are showing compassion in the novels and the sequential order of the events which are driven by psychology compassion in these three novels. The novel A Tale of Two Cities actions are going in France, during the French revolution, while David Copperfield and Oliver Twist are starting in England. David Copperfield was said to be the autobiography of the novelist Dickens himself, and the compassion is shown in multiple personalities, specifically his aunt, his first love Dora, and her second love Agnes. Whereas compassion, in Oliver Twist, offered by the personalities is starting from the doctor in the orphanage sponsored by the Diocese where her mother has started the story before she is giving birth to Oliver and die. Compassion is shown in different characters even in some criminals. However, the novel A Tale of Two Cities has clearly the main characters like Draney and Lucie who will finally live a happy life due to the compassion of several characters mainly Cartoon. To sum up, compassion is one of the important novel’s parts, even in some evil or changing characters. Its psychology is complex to study along with its impact on novel actions.